IMPLEMENTASI STRATEGI THINK-TALK-WRITE (TTW) PADA PEMBELAJARAN MENULIS DAN PEMAHAMAN MATEMATIS - Kadarwati, Sri; Sulistyaningsih, Nining (Jurnal Pendidikan, 2009)
This study examines whether students' ability in mathematical writing and understanding gained from teaching through "think talk write' strategy is better than students' ability gained from conventional one.; This study also examines students' ability in mathematical writing and understanding from gender aspects. Using quantitative design, data was taken through documentary study, questioner sheets and observation. Data was analyzed using two ways ANOVA. Result shows: a) the ability of students in mathematical writing and understanding gained from conventional one; b) the ability of female students is better tan male students; and c) Think Talk Write strategy can improve students' mathematival disposition ability.